KEKUASAAN DAN KONFLIK IDEOLOGI DALAM FILM KUPU-KUPU KERTAS: ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH - Fany Anggria (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study examines power and ideological conflict in the film Kupu-Kupu Kertas through the Critical Discourse Analysis (CDA) approach developed by Norman Fairclough. The film reflects the historical tension between the Indonesian Communist Party (PKI) and Nahdlatul Ulama (NU) in 1965 in Banyuwangi, framed through a love story between two characters from opposing ideological backgrounds. Drawing on Foucault’s theory of power-knowledge relations and Gramsci’s concept of ideological hegemony, this research explores how power discourse is constructed through the film’s textual elements, discursive practices, and social context. The novelty of this study lies in its choice of a rarely examined object and its distinct historical-political focus, differing from previous studies that explored power issues within the contexts of family, gender, or political speeches. The findings are expected to enrich critical studies on the representation of ideology and power in texts as instruments of ideological domination that shape public perception and interpretation of history and socio-political realities.